The Book of Senior Jokes : (The Ones You Can Remember) - Tibballs, Geoff (London Michael O'Mara Books Ltd., 2010)
JOKES & RIDDLES. Ageing is one of those unavoidable facts of life, and what more can you do about it than laugh (admittedly, slightly defensively)? Just why fading physical and mental faculties should be so funny is something of a mystery, but they are and with The Book of Senior Jokes you can laugh off your forgetfulness, fading physique and new penchant for the afternoon nap. This book - and do, please, try to remember to pay for it - is a collection of the very best 'senior' jokes, putting them down between hard covers where even you can't forget them. The Book of Senior Jokes is the perfect present for anyone feeling their age, no matter how old they may be, that will help them celebrate all that is positive - and positively hilarious - about growing older.